Case report: Conservative treatment for fertility preservation in a woman with hemoperitoneum due to an invasive mole - Xu, Linjuan; Feng, Min; Cai, Jing; Li, Hongmei (Frontiers in Oncology, 2022)
Background: Invasive moles are a subtype of gestational trophoblastic neoplasia (GTN) that usually develops after hydatidiform molar pregnancies. Uterine rupture in high-risk GTN is a rare and potentially catastrophic event. The treatment of invasive mole perforation with uterine rupture is particularly challenging in young women who desire fertility. Case presentation: We present the case of a 22-year-old woman with a rapidly transformed invasive mole after two evacuations for a complete molar pregnancy. Within 21 days of the second molar evacuation, the serum β-hCG level surged from 5,718 mIU/ml to 444,617 mIU/ml. An ultrasonography examination showed the uterus was 9.2×8.9×7.8 cm in size with an uneven echo area of 6.9×5.2 cm near the fundus of the uterine cavity; the convex anterior wall had no normal muscle layer, and the outer margin was about 0.24 cm from the serosal layer. The patient was diagnosed with an invasive mole. Since she desired fertility preservation, we proposed a methotrexate (MTX) chemotherapy regimen. Before the planned chemotherapy, she experienced sudden abdominal pain accompanied by a blood pressure of 76/48 mmHg and a pulse rate of 116 bpm. An emergency abdominal ultrasound scan showed acute intra-abdominal bleeding (approximately 2,000 ml), and blood tests showed a hemoglobin concentration of 7.9 g/dL. Immediate uterine artery embolization was performed, and 35 mg MTX was administered bilaterally through the uterine arteries. The next day, the serum β-hCG decreased to 83,530 mIU/ml, and the vital signs remained stable. Seven days later, the patient received a combination of etoposide, methotrexate, dactinomycin, cyclophosphamide, and vincristine (EMACO), and the serum β-hCG level normalized after cycle five. At the 13-month follow-up after therapy completion, the woman was disease-free with a normal β-hCG level. Conclusion: Our experience highlights the potential feasibility and efficacy of conservative treatment for fertility preservation in such scenarios.